Features of the development of the potential of Russian human capital in the context of sanctions - R. M. Ustaev (Вестник Северо-Кавказского федерального университета)
Introduction. Research on human capital occupies a central place in modern scientific discourse. In the context of unprecedented sanctions pressure on Russia, strengthening and building up human capital is becoming a critically important factor in ensuring economic sustainability. The assessment of the quality of human capital in Russia in recent years has revealed an increase in this indicator, however, the sanctions imposed against Russia necessitate accelerated measures to further strengthen human capital and increase its potential.Goal. Highlighting the problems of development and prospects for increasing the Russian potential of human capital in the context of external sanctions.Materials and methods. The study is based on the analysis of situational and systemic approaches, which allowed us to identify opportunities for the growth of human capital potential in new conditions.Results and discussion. The importance of human capital development for innovative economic growth is substantiated. There is a direct link between the development of human capital and investments in education, science, healthcare and professional development, which allows increasing labor productivity, stimulating innovative processes and increasing human competitiveness in the market. The indicators of the assessment of the innovative component of human capital in the country are presented. The directions of human capital development in the economy under the conditions of sanctions pressure are given.Conclusion. Based on the results of the study, it can be concluded that the programmatic approach to the development of human capital potential involves systematic planning and implementation of measures aimed at its integrated development, taking into account external factors. Using a programmatic approach to the development of human capital, the state and business can create a favorable environment for realizing the opportunities of each person and ensuring the prosperity of the whole country.